2021
DOI: 10.54113/j.sust.2021.000009
|View full text |Cite
|
Sign up to set email alerts
|

Review on mechanical behavior of solar cells for building integrated photovoltaics

Abstract: The energy crisis and environmental pollution have promoted the rapid development of renewable solar technology. Building integrated photovoltaics (BIPV) is an important field for the future development of solar energy. This review presents the mechanical property studies of existing BIPV and analyzes its research status to offer advice for engineering applications. By analyzing the types and mechanical characteristics of solar cells in the existing BIPV and determining the load conditions that need to be cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Studies have shown that the composition of straw is similar to that of bamboo [61][62][63][64] and wood [65,66]. Therefore, it can be considered as an alternative raw material for wood and bamboo [67][68][69]. Straw products mainly include wheat straw particleboard, straw MDF, wheat straw fiberboard, grasswood composite MDF, soft straw board, lightweight composite wall material, straw charcoal, straw plastic composite material [70].…”
Section: Straw-based Panelsmentioning
confidence: 99%
“…Studies have shown that the composition of straw is similar to that of bamboo [61][62][63][64] and wood [65,66]. Therefore, it can be considered as an alternative raw material for wood and bamboo [67][68][69]. Straw products mainly include wheat straw particleboard, straw MDF, wheat straw fiberboard, grasswood composite MDF, soft straw board, lightweight composite wall material, straw charcoal, straw plastic composite material [70].…”
Section: Straw-based Panelsmentioning
confidence: 99%
“…The energy problem of modern buildings is quite serious [112], but engineered wood can alleviate this problem to a certain extent, and in this context MPCs have also been improved. Raw wood is formed into engineered wood after a series of chemical and physical processes, which have the advantages of environmental friendliness, high performance, and standardization [113][114][115][116][117] and it has been widely used in different types of timber buildings [118,119].…”
Section: Conservatory Measurementioning
confidence: 99%
“…The elastic constant of wood and its solid wood composite material is the quantity that characterizes the elasticity of the material (Yi 1996;Wang et al 2014;Li et al 2016;Li et al 2020;Li et al 2021;Li et al 2021;Ponzo et al 2021). Many researchers have studied the mechanical properties of wood (Ma 1996;Zhou et al 2007;Cheng and Wang 2015;Wang et al 2019;Felice et al 2021), and static and dynamic methods have yielded results in testing its modulus of elasticity, shear modulus, and Poisson's ratio Wang et al 2016;Zahedi et al 2020;Li et al 2021a,b;Tang et al 2021;Wang and Ghanem 2021;Meng et al 2021;Zhou et al 2021). Many research studies used probabilistic methods to study the mechanical properties of materials (Fan and Shen 1992;Thomas 2003; Kumpenza et al 2018;Peng et al 2018; Wang and Roger 2021; Wang and Roger 2022).…”
Section: Introductionmentioning
confidence: 99%